VitaSi: A Real-Time Contactless Vital Signs Estimation System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In recent decades, measuring vital signs has been a popular topic for many researchers. The system for monitoring vital signs benefits humans in many aspects, such as patient health care and disease prevention for elderly people. As important vital signs, the heart rate and breathing rate, which is also called respiration rate (RR), have been attracting increasing attention and many methods for heart rate (HR) and breath rate (BR) detection have been proposed. The methods for measuring the HR and BR can mainly be divided into contact methods and non-contact methods. Contact methods, as the traditional techniques, are the most widely used measurement methods for signs because of their high accuracy.